Preparation and oxidation behaviour of MoSi2-SiC-Si-ZrB2 composite coatings on carbon surface via laser cladding. (17th November 2022) - Liu, Xuemei; Chen, Weixin; Tao, Xueyu; Fan, Heliang; Liu, Zhangsheng; Ling, Yihan; Guo, Litong
ABSTRACT: Anti-oxidation coatings of MoSi2 -SiC-Si-ZrB2 were prepared on the graphite surface by laser cladding. The XRD, scratching bonding force, SEM and isothermal oxidation tests were used to investigate the microstructure and properties of the coatings. The coating with 40 wt% ZrB2 added (MoSi2 :SiC:Si:ZrB2  = 16:4:5:16.6) has the lowest degree of oxidation, the best oxidation resistance and the highest bonding strength between coating and matrix. The scratching bonding force still maintained at about 9.9 N after laser ablation, and there were no obvious destructive defects but some pores and cracks on the coating. After a Si-enriched amorphous layer was formed, the relative oxygen permeability was significantly decreased and the oxidation of the coating was passivated, which prevented the matrix from further oxidation.